The bilingual gap in children's language, emotional, and pro-social development - Cobb-Clark Deborah A. (Sciendo, 2021)
In this paper we examine whether – conditional on other child endowments and family inputs – bilingual children achieve different language, emotional, and pro-social developmental outcomes. Our data, which allow us to analyze children's development in a dynamic framework, are extracted from the UK Millennium Cohort Study (MCS). We model the development production functions for bilingual children using cumulative value-added specifications, which account for parental investments and children's own ability. Analysis based on child age confirms that bilingual children initially have worse language skills than their monolingual peers. The commencement of schooling appears to attenuate these differences, and by age seven, bilingual children have a developmental advantage. We find evidence of a positive relationship between bilingualism and some aspects of emotional development, and it is mainly boys who appear to benefit from their bilingual background.